Synthesis of some substituted 1,3,4-oxadiazoles, 1,3,4-thiadiazoles and 1,2,4-triazoles from 2-(2,3-dimethylphenyl amino) benzoic acid - Khalid Daoud; Shereen Mohamed; Nagham Al-Niami (College of Education for Pure Sciences, 2009)
ABSTRACT In this paper the synthesis of some substituted 1,3,4-oxadiazoles, 1,3,4-thiadiazoles and 1,2,4-triazoles was achieved. 2-(2,3-dimethyl phenyl amino) benzoic acid was esterified to its ethyl ester by its reaction with absolute ethanol in presence of concentrated sulfuric acid. The ethyl ester was treated with hydrazine hydrate in ethanol to give the corresponding hydrazide. The hydrazide was converted to substituted thiosemicarbazide by its reaction with ammonium thiocyanate. The thiosemicarbazide was treated with sodium hydroxide solution and with sulfuric acid to give 5-(2,3-dimethyl phenyl amino phenyl)-1,2,4-triazole-3-thiol and 2-(2,3-dimethyl phenyl amino phenyl)-5-amino-1,3,4-thiadiazole respectively. The acid hydrazide was treated with substituted benzaldehyde to give hydrazones which cyclized to disubstituted 1,3,4-oxadiazole, while the reaction of hydrazide with formic acid followed by cyclization of formyl hydrazine by PbO2 to give monosubstituted 1,3,4-oxadiazole. Finally, treatment of hydrazide with carbon disulfite in alcoholic potassium hydroxide gave 2-(2,3-dimethyl phenyl amino phenyl)-1,3,4-oxadiazole-5-thiol. The structures of the synthesized compounds were confirmed by physical and spectral means.